Study of changes in lipid profile and insulin resistance in Egyptian patients with chronic hepatitis C genotype 4 in the era of DAAs. Issue 1 (1st January 2018) - El Sagheer, Ghada; Soliman, Elwy; Ahmad, Asmaa; Hamdy, Lamiaa
ABSTRACT: Chronic hepatitis C virus (HCV) infection is associated with altered metabolism, including dyslipidemia and insulin resistance. These contribute to disease progression and influences the response to therapy. To investigate the relationships of new direct-acting antiviral drugs, simeprevir/sofosbuvir, with lipid profile and insulin resistance (IR). Eighty chronic hepatitis C genotype 4 patients were included; they were divided into four groups according to the severity of fibrosis as detected by fibroscan. Forty healthy persons volunteered as a control group. Lipid profile changes and IR were analyzed at baseline and after the end of treatment, and any effect of these changes on the response to treatment was studied. Before treatment, the levels of serum triglycerides were significantly higher in patients than in the control, and the levels of fasting insulin showed a progressive increase with advancing stage of fibrosis. At the end of treatment, there were a significant reduction in serum triglycerides, FBS, fasting insulin, and homeostasis model for the assessment of IR ( P < 0.001), and a significant elevation of serum cholesterol and low-density lipoprotein (LDL)-c, high-density lipoprotein (HDL)-c, and LDL/HDL ratio ( P = 0.001). An end-of-treatment response (week 12) was achieved in (99%) of the treated cases with 99% sustained viral response for 12 weeks post-treatment (week 24). Significant lipid profile changes were detected at the end of treatment. Serum lipid levels and IR are no longer predictors of response to DAAs. Follow-up of the lipid profile is warranted to avoid any possible remote effect of atherosclerotic heart disease.